2003
DOI: 10.1093/ndt/gfg407
|View full text |Cite
|
Sign up to set email alerts
|

Tubular staining of modified C-reactive protein in diabetic chronic kidney disease

Abstract: The present group of diabetic patients showed progressive tubular mCRP staining with declining renal function and increasing severity of histological lesions. Further studies in less proteinuric patients should clarify whether tubular mCRP expression constitutes a progression factor. It also needs to be demonstrated whether mCRP accumulates in tubuli to further stimulate interstitial fibrosis or is mandatory for the resolution of the process. Since mCRP staining was independent of proteinuria we suggest that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 24 publications
6
45
0
3
Order By: Relevance
“…This is consistent with previous findings and would enable anti-CRP autoantibodies to interfere with biofunctions of mCRP, since these autoantibodies bind mCRP rather than pentameric CRP [27,[29][30][31].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with previous findings and would enable anti-CRP autoantibodies to interfere with biofunctions of mCRP, since these autoantibodies bind mCRP rather than pentameric CRP [27,[29][30][31].…”
Section: Discussionsupporting
confidence: 93%
“…However, since anti-CRP antibodies in SLE are not directed against the circulating pentameric form of CRP but rather to CRP monomers, a more likely pathogenic potential of circulating anti-CRP would be to target tissue-bound monomeric CRP (mCRP) [22]. Such mCRP has been detected in vessels, skeletal muscle, liver and in tissue of chronic renal disease, possibly with extrahepatically produced CRP [29][30][31][32]. The well-known fact that pentameric CRP activates the classical complement pathway, has also been reported to account for mCRP [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…This has led us to propose that the dissociation of the CRP molecule is an activating mechanism that is required for the expression of enhanced bioactivities and is also a buffering mechanism that localizes the actions of mCRP into inflammatory loci to prevent the possible global effects directly induced by large-scale alterations in the serum levels of CRP [73]. Consistent with our proposal, immunohistochemical analyses using highly specific antibodies revealed that mCRP, not CRP, was the major isoform present in local lesions, including atherosclerotic plaques [55,76], diabetic kidneys [77] and stroke neovessels [78].…”
Section: Dissociation Of Crp Localizes the Enhanced Bioactivitiessupporting
confidence: 83%
“…After tissue damage during the acute-phase reaction, the serum concentration of native, pentameric CRP increases while the monomeric tissue form of CRP may also appear. Indeed, mCRP has been shown to be present in the kidneys of diabetic patients in tubular localization 31 and in atherosclerotic plaques in colocalization with complement proteins. 32,33 Once CRP becomes surface-bound to its ligands the binding site for C1q opens on the disc, resulting in activation of the classical complement pathway.…”
Section: Discussionmentioning
confidence: 99%